Sharing the decarbonisation effort: getting Eastern Mediterranean and Middle East countries on the road to global carbon neutrality - Yiakoumi, Despina; Taliotis, Constantinos; Zachariadis, Theodoros; Griffiths, Steven (My University, 2023)
To achieve the Paris Agreement’s goals of keeping the global temperature rise well below 2 °C, or even better below 1.5 °C, relative to pre-industrial levels by the end of this century, countries need to make fair and ambitious contributions to reducing their greenhouse gas emissions. Here, three clusters are proposed that encompass fourteen approaches derived from three main equity principles to determine equitable national emission allocations in the year 2030 for the seventeen countries in the Eastern Mediterranean and Middle East (EMME) region. The allocations are compared with the Nationally Determined Contributions of each country in order to assess the degree to which current EMME climate change mitigation targets are sufficient. The results suggest two approaches that may be considered both realistic and fair, although with the caveat that both rich and poor EMME countries may still have reason to resist the allocations indicated by these approaches. One of these two approaches relates to the principle of responsibility and the other relates to a combination of capability and responsibility. Both require emissions in the EMME region to drop by nearly 50% by 2030 as compared to 2019 levels so as to be in line with a 1.5 °C warming scenario.
Keywords: climate change mitigation; decarbonisation; effort sharing; emission reductions; EMME region; equity